IMPLEMENTASI ALGORITMA BREADTH FIRST SEARCH PADA PACMAN UNTUK MENGATUR PERGERAKAN KARAKTERImplementasi Algoritma Breadth First Search Pada Pacman Untuk Mengatur Pergerakan Karakter - Ulza Alkindi; Nur Akhmad; Yogo Kartiko; Triono Putro; Rumini Rumini (JURIKOM (Jurnal Riset Komputer), 2018)
Artificial intelligence is an important factor in games between humans against computers (NPC = Non-Character Player). One method of artificial intelligence that can be used is the Breadth First Search (BFS) algorithm and fuzzy logic. This study chose the classic Pac-Man game, in the game the Pac-Man BFS algorithm was applied to the process of finding and pursuing Pac-Man. For fuzzy logic, the Sugeno method is used when making decisions, namely ghost behavior in the game. The methodology used is the prototype methodology. In the testing process, the BFS algorithm is used in the black box testing technique, while the Sugeno fuzzy logic method is used to compare computation testing during decision making. With the testing process, it can be drawn that the appropriate BFS algorithm to find the shortest path while pursuing Pac-Man and Sugeno Fuzzy Logic method can be used for ghost behavior decision making with search speed 10 times faster than DFS algorithm.